2009
DOI: 10.1007/s10753-009-9125-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Inhibits MMP-2 and MMP-9 Expression and Activity Through PPARα/γ and TIMP-1-Mediated Mechanisms in Cultured Mouse Celiac Macrophages

Abstract: Aspirin is an anti-inflammatory drug, and has been widely used for the prevention of cardio-cerebrovascular events. Matrix metalloproteinase (MMP)-2 and MMP-9 can degrade the extracellular matrix and may be critical for the development and disruption of atherosclerotic plaques, while tissue inhibitor of metalloproteinase (TIMP)-1 may inhibit the degradation of extracellular matrix. The purpose of present study was to investigate the inhibitory effects of aspirin on MMP-2 and MMP-9 expression and activity in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…A previous study has demonstrated that aspirin, together with its anti-platelet activity, suppressed vascular inflammation and increased the stability of atherosclerotic plaques in murine atherosclerosis, thus exhibiting an anti-atherogenic effect (37). Aspirin can inhibit the expression and release of MMP-2/9 by upregulation of PPARα/γ gene expression, and also inhibit the activity of MMP-2/9 by induction of TIMP1 expression, which may be beneficial for the stabilization of atherosclerotic plaques (38). However, to the best of our knowledge, no studies have reported the potential effects of aspirin on MMP-9 expression in TNF-α-treated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that aspirin, together with its anti-platelet activity, suppressed vascular inflammation and increased the stability of atherosclerotic plaques in murine atherosclerosis, thus exhibiting an anti-atherogenic effect (37). Aspirin can inhibit the expression and release of MMP-2/9 by upregulation of PPARα/γ gene expression, and also inhibit the activity of MMP-2/9 by induction of TIMP1 expression, which may be beneficial for the stabilization of atherosclerotic plaques (38). However, to the best of our knowledge, no studies have reported the potential effects of aspirin on MMP-9 expression in TNF-α-treated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some anti-inflammatory drugs also alter MMP-9 and TIMP-1 expression and function. For example, aspirin was shown to inhibit MMP-9 activity by inducing the expression of TIMP-1 in cultured mouse celiac macrophages (Yiqin et al 2009). Thus, the inhibition of MMP-9 by LXA 4 ME may be caused by enhancing the expression of TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…During inflammatory response, MMPs produced by macrophages also play important roles and contribute to infiltration of leukocytes into tissues[7, 8, 21]. Therefore, we investigated the effects of BER on LPS-induced MMP-2 and MMP-9 expression, as well as secretion by macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…In order to comprehensively clarify the anti-inflammatory activity of BER, we determined the effects of BER on the expression of COX2 and PGE2 production, which results show that BER also intensively inhibits the expression of COX2 and PGE2 production by macrophages. In addition, macrophages can release MMPs to facilitate infiltration of immune cells during inflammatory response[7, 8]. So we also evaluated the effects of BER on the expression and secretion of MMP2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%